Nursing Theories Are In Main Headlines of Courses, But There Is No Trace Of Their Application In The Practice - Reza Saadat Mehr; َAkram Sanagoo; Leila Jouybari (مجله ایرانی آموزش در علوم پزشکی, 2020)
Letter to Editor